Business to it Model Canvas: proposição de um framework para construção de Business Case de projetos de Tecnologia da Informação - Fey, Wecsley (Universidade do Vale do Rio dos Sinos, 2022)
Organizations are increasingly seeking Information Technology (IT) solutions to enhance their business processes and consequently their results, requesting the execution of IT projects that aim to solve problems and leverage their performance and competitiveness in the market. In turn, the Information Technology areas need to provide satisfactory solutions to these problems and needs of the organizations. This scenario denotes and represents the need for partnership and communication between these areas, with the objective of requesting and delivering solutions that meet the required organizational objectives. This study aims to present a solution proposal to guide organizations in creating business cases for Information Technology projects, fostering their alignment and communication between business areas and IT, thus promoting better understanding and meeting business needs. To enable the arrival of the results, the Design Science Research method was used, which resulted in the conception of an artifact that aims to help organizations in the execution of this process. Following the steps of the chosen method, the solution created went through an evaluation stage, putting into practice its use within a real context with the goal of ensuring that the proposed solution has adherence and significant contribution to the organizations. At the end of the work, it can be concluded that the conceived artifact is an important and useful solution proposal, which effectively contributed to the elaboration of specific business cases for information technology projects and consequently favoring the alignment between the business and IT areas, since this artifact, through its results, can directly contribute to a better request and understanding of the organization in relation to the needs and deliveries of IT projects, shaping and guiding the structure of thought for the conception of new information technology projects.
Keywords: Tecnologia da informação; Cases de negócio; Projetos; Alinhamento estratégico; Design Science Research (DSR); Information technology; Business case; Projects; Strategic alignment; ACCNPQ::Ciências Sociais Aplicadas::Administração